Emissive Synthetic Cofactors: Enzymatic Interconversions of tzA Analogues of ATP, NAD+, NADH, NADP+, and NADPH. (21st December 2017) - Hallé, François; Fin, Andrea; Rovira, Alexander R.; Tor, Yitzhak
Abstract: A series of enzymatic transformations, which generate visibly emissive isofunctional cofactors based on an isothiazolo[4, 3‐ d ]pyrimidine analogue of adenosine ( tz A ), was developed. Nicotinamide adenylyl transferase condenses nicotinamide mononucleotide and tz ATP to yieldN tz AD +, which can be enzymatically phosphorylated by NAD + kinase and ATP or tz ATP to the correspondingN tz ADP + . The latter can be engaged in NADP‐specific coupled enzymatic transformations involving conversion toN tz ADPH by glucose‐6‐phosphate dehydrogenase and reoxidation toN tz ADP + by glutathione reductase. TheN tz ADP + /N tz ADPH cycle can be monitored in real time by fluorescence spectroscopy.